2021
DOI: 10.1021/acsanm.1c01908
|View full text |Cite
|
Sign up to set email alerts
|

Ni Nanoparticles on Ni Core/N-Doped Carbon Shell Heterostructures for Electrocatalytic Oxygen Evolution

Abstract: Supported Ni-based nanocatalysts have attracted much attention to replace noble metal catalysts (e.g., IrO2) for the oxygen evolution reaction (OER) due to their low costs. However, their low activity is the main hindrance for their use in the practical OER application. In this study, a Ni-based core–shell material (Ni@Ni-NC) is produced through the heat treatment of a mixture of urea and NiCl2·(H2O)6. Multiple analysis data reveal that the Ni@Ni-NC consists of a Ni nanoparticle core and several tens of nanome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 66 publications
(104 reference statements)
1
17
0
Order By: Relevance
“…Transmission electron microscopy (TEM) and high-resolution TEM (HRTEM) images of Cu SACs/NG (Figure a,b) demonstrated that the wrinkled structure was well maintained in comparison with the pristine graphene shown in Figure S1 (see Supporting Information, SI), and an absence of visible particles could be observed. The lattice fringe is measured to be ∼0.34 nm from the wrinkles in the HRTEM image (Figure b), which is in good agreement with the (002) crystalline plane of graphene . The selected area electron diffraction (SAED) pattern (inset in Figure b) revealed two concentric rings with diffraction radii of ∼0.34 nm and ∼0.20 nm corresponding to the (002) and (101) planes of graphene, respectively .…”
Section: Results and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Transmission electron microscopy (TEM) and high-resolution TEM (HRTEM) images of Cu SACs/NG (Figure a,b) demonstrated that the wrinkled structure was well maintained in comparison with the pristine graphene shown in Figure S1 (see Supporting Information, SI), and an absence of visible particles could be observed. The lattice fringe is measured to be ∼0.34 nm from the wrinkles in the HRTEM image (Figure b), which is in good agreement with the (002) crystalline plane of graphene . The selected area electron diffraction (SAED) pattern (inset in Figure b) revealed two concentric rings with diffraction radii of ∼0.34 nm and ∼0.20 nm corresponding to the (002) and (101) planes of graphene, respectively .…”
Section: Results and Discussionsupporting
confidence: 92%
“…The lattice fringe is measured to be ∼0.34 nm from the wrinkles in the HRTEM image (Figure 3b), which is in good agreement with the (002) crystalline plane of graphene. 38 The selected area electron diffraction (SAED) pattern (inset in Figure 3b) revealed two concentric rings with diffraction radii of ∼0.34 nm and ∼0.20 nm corresponding to the (002) and (101) planes of graphene, respectively. 39 The well concentric rings confirmed the presence of graphene without any highly crystallized phases of Cu catalysts.…”
Section: Resultsmentioning
confidence: 78%
“…As shown in Figure b, the N 1s XPS spectrum of NCQDs-500 is well divided into two peaks at 398.6 and 400.4 eV corresponding to pyridinic-N and pyrrolic-N, respectively . However, the N 1s XPS spectrum of Ni@NCQDs-500, as shown in Figure c, is divided into four peaks at 398.08, 398.88, 399.78, and 401.08 eV corresponding to pyridinic-N, N–Ni, pyrrolic-N, and graphitic-N, respectively; , the atomic content of nitrogen by XPS element analysis was found to be 5.46%. The existence of N–Ni with a binding energy similar to that of pyridinic-N also proves that Ni species have interacted with N species on the surface of NCQDs.…”
Section: Resultsmentioning
confidence: 95%
“…The performance of the charge cycle and the discharge were consistently attributed to the substantial lithium storage capacity of the electro-spun composite. The fibers also have a good rating capacity, and the electrical impedance also diminishes as the number of cycles climbs [ 118 , 119 , 120 ].…”
Section: Advancements In Electrospun Anode Materialsmentioning
confidence: 99%